Type 2 Diabetes and Oxidative Stress and Inflammation: Pathophysiological Mechanisms and Possible Therapeutic Options - Cristina Vassalle; Melania Gaggini (MDPI AG, 2022)
Type 2 diabetes (T2D) is a public health burden associated with high healthcare and societal costs and elevated morbidity and mortality [...]